Comparison of the reliability of peak force measured during an isometric mid-thigh pull and isometric squat - Brady, C. J.; Harrison, A. J.; Flanagan, F. P.; Comyns, T. M. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to compare peak force produced during the isometric midthigh pull (IMTP) and isometric squat (IsoSquat), performed at the same knee and hip angles (135 - 140°) and determine the reliability of both tests. Following a specific warmup, 22 international athletes from different sports performed 2 maximal effort tests of both the IMTP and IsoSquat. Peak force achieved during the IsoSquat was significantly greater (p = 0.01) than peak force achieved during the IMTP. Both tests were highly reliable for peak force. Therefore, strength and conditioning coaches can select either test when examining lower extremity maximum strength. However, the IsoSquat produces higher peak force values and this may be a more accurate reflection of the athlete`s maximum strength.